PENYELESAIAN SENGKETA EKONOMI SYARIAH SECARA LITIGASI DI PENGADILAN AGAMA METRO KELAS IA - Intan Pelangi M. Sofwan Taufiq MirantiDwiCahyani (Muhammadiyah Law Review Journal, 2022)
Along with the development of the era of growth and development of Islamic Financial Institutions (LKS) in Indonesia is now increasingly rapidly. The rapid development of Islamic banking and financial institutions also has an impact on the greater possibility of problems or disputes between related parties such as service providers and the people being served.The problems of this research are as follows: 1. How is the settlement of sharia economic disputes in litigation with Case Number 0431/Pdt.G/2020/PA.Mt in the Metro Religion Court Class IA?. 2. What is the judge's decision on the settlement of sharia economic disputes in litigation with Case Number 0431/Pdt.G/2020/PA.Mt at the Metro Religion Court Class IA?.The research method in this thesis is by using the Juridical Empirical method and by conducting interviews with sources.There are two criteria in handling sharia economic disputes, namely handling ordinary events and handling simple events. The handling of sharia economic cases in a simple way refers to the Supreme Court Regulation Number 2 of 2015, concerning the Simple Lawsuit Procedure. Handling of ordinary events that refers to HIR (Java and Madura) and RBg (outside Java and Madura) as the legal procedure. Examination of the usual event begins at the stage of the first trial, which is to summon the two parties to the dispute and then make mediation efforts first. If mediation fails, the trial will continue at the stage of reading the lawsuit and then proceed with reading the exception then the answer stage between the defendant and the defendant, namely the replica and duplicate. After the answer stage, the next stage is evidence by both parties, after proof both parties provide conclusions from each party, and the final stage of the trial is the decision by the panel of judges. Judges in the Religious Courts including the Metro Religious Courts class IA in making decisions on a case being examined using the stages, namely the formulation of the problem or main dispute, data collection in the evidentiary process, data analysis to find facts, legal discovery and application, and decision making. decision.The conclusions in this study are: 1. Settlement of sharia economic disputes in litigation with Case Number 0431/Pdt.G/2020/PA.Mt at the Metro Religious Court Class IA, carried out with the usual program which begins at the first trial stage, which begins with the summons of the parties. The defendant then continued with the mediation process with the results of the mediation being unsuccessful, so that it was continued on the agenda of the next session of reading the plaintiff's lawsuit, then followed by reading the exception from the defendant, and ending with the reading of the decision on the exception. 2. The judge's considerations in the case register number 0431/Pdt.G/2020/PA.Mt, namely: based on the opinion of legal experts that the lawsuit must basically contain the formal requirements for the identity of the parties, posita and petitum. Claims must be made carefully, clearly, concisely, concisely, and clearly. The decision on the case register Number 0431/Pdt.G/2020/PA.Mt is based on the judge's consideration, namely rejecting the lawsuit.Suggestions that the author can give are: 1. There are many legal rules contained in various laws and regulations which have a point of contact with Law Number 3 of 2006. Therefore, it is better for judges of the Religious Courts to continue to study and understand them to be used as guidelines in deciding sharia economic cases, whether related to bank Indonesia, related to religious courts, and other laws that are still related to sharia economics. 2. In connection with the process of resolving this shari'ah economic dispute, the Metro Religious Court Class IA should be able to explore the values and norms of Islamic law, both those contained in the Qur'an, al-Sunnah and other books. fiqh/ushulfiqh and the fatwas of the Ulema Council which in this case is through the National Syari'ah Council relating to issues surrounding the sharia economy.